IgE Cross-Reactivity between Humulus japonicus and Humulus lupulus - Jeong, Kyoung Yong; Lee, Jongsun; Mistrello, Gianni; Park, Kyung Hee; Park, Jung-Won (Yonsei medical journal, 2018)
Japanese hop (Humulus japonicus) is a major cause of weed pollinosis in East Asia. However, supplies of commercial allergen extract from this plant have not met clinical demand. The pollen of common hop (Humulus lupulus), a closely related species, may provide an alternative source if there is strong IgE cross-reactivity between these two species. We aimed to compare the IgE cross-reactivity and allergenicity of common hop and Japanese hop pollen. Cross-reactivity was measured by inhibition ELISA. One- and two-dimensional (2D) gel analyses combined with IgE immunoblotting and mass spectrometry [liquid chromatography coupled to electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS)] were performed to detect IgE-reactive pollen components. Up to 16.7% of IgE reactivity to Japanese hop was inhibited by common hop. A 12-kDa protein component of Japanese hop pollen that showed the most potent IgE reaction was absent from common hop. Six IgE-reactive components from Japanese hop were detected by 2D gel electrophoresis and LC-ESI-MS/MS, but showed low Mascot scores, preventing positive identification. No significant IgE cross-reaction was observed for Japanese and common hop pollen allergens. Development of allergy diagnostic and immunotherapeutic reagents based on Japanese hop pollen are urgently needed.